Le programme de recherche ANR « Cinémarchive » (décembre 2007-décembre 2010) - Marc Vernet (Mise au Point)
The ANR research program "Cinémarchive" which was accepted on December 24, 2007 brought together for three full years five institutions plus one: the Universities of Paris Diderot, of Paris 3, Montpellier 3 Paul Valery, the Ecole Nationale Supérieure Ulm, and the French Cinémathèque. The Institute Jean Vigo associated with Montpellier 3 also participated in the program. The composition of the group demonstrated the express desire of the group to center its research on archival work which had already been started first for collections labeled as non-film, and to carry out collective historical, esthetical, and methodological research.The group included twelve senior researchers and the archivists of two patrimonial institutions. This configuration showed not only the multidisciplinary approach necessary in research on the cinema but also the new context of collaboration between conservation, research, and the training of young researchers. In 2008-2009 there should be master’s and doctoral students working on several of the selected collections.The collections in question come from the Triangle Film Corporation, from the decorators Max and Douy, Serge Pimnoff, cinema photographers Georges Pierre, Raymond Cauchetier and Vincent Rossell, from the scriptwriter Lucie Lichtig for the scenario of Lola Montes.